Avaliação automatizada de uma habilidade motora fundamental com o kinect - Sulino, Rafael Macedo [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The assessment of the human body displacement is essential for both, the academic scientific research and the professional practice, especially with regard to the assessment of fundamental movement patterns (FMP) throughout childhood in order to identify possible delays and provide adequate motor intervention. Technologies available recently in the entertainment market, as the Kinect sensor, have great potential for application in several areas, especially with regard the capture and movement analysis, enabling the acquisition of data quickly and efficiently without the use of markers, and at low cost compared to high precision systems available in the Laboratories. In this study we propose a system based on Kinect for automated assessment of the FMP standing long jump. The study was conducted in two stages, including the construction, testing and implementation of the system. The first stage, related to the construction of the system, consisted of the development of algorithms necessary for the acquisition, storage, processing and analysis of data, and the second stage consisted of three experimental studies. In the first study we evaluated the Kinect for static data acquisition, in comparison with the Optotrak, a high precision optical system, with the aim of assessing the accuracy of the device on variation in the capture of three-dimensional coordinates and measure of angles agreement with a high precision laboratory system. The results indicated minimal variation in data acquisition related to fixed points for 50 seconds, and high correlation measures when compared to the Optotrak. In the second study we evaluate the Kinect for dynamic data acquisition, comparing it again with Optotrak in five different joint displacements, and three different speeds. The results indicated that the difference between the measurements obtained from the Kinect compared with the measurements obtained from the Optotrak are within a confidence interval...

Avaliar o movimento do corpo humano é essencial tanto na pesquisa acadêmica quanto na prática profissional, principalmente no que diz respeito a avaliação de habilidades motoras fundamentais ao longo da infância, a fim de identificar possíveis atrasos e possibilitar intervenção motora adequada. Tecnologias recentemente disponibilizadas no mercado de entretenimento, como o sensor Kinect, apresentam grande potencial para aplicação nas mais diversas áreas, de modo especial no que diz respeito à captura e análise de movimentos corporais possibilitando a aquisição de dados de forma rápida e eficiente, sem utilização de marcadores, e com baixo custo comparado a sistemas de alta precisão disponíveis no mercado. No presente estudo propomos um sistema baseado no Kinect para avaliação automatizada do PFM salto horizontal. O estudo foi realizado em duas etapas, abrangendo a construção, teste e aplicação do sistema. A primeira etapa, de construção do sistema, consistiu na elaboração dos algoritmos necessários para a aquisição, armazenamento, tratamento e análise dos dados, e a segunda etapa consistiu na realização de três estudos experimentais. No primeiro estudo avaliamos o Kinect para aquisição de dados estáticos, comparando-o com o Optotrak, um sistema óptico de alta precisão, que permitiu avaliar a precisão do Kinect no que diz respeito à variação na captura de coordenadas tridimensionais e concordância na medida de ângulos com um sistema de alta precisão de laboratório. Os resultados indicam variação mínima na coleta de dados referentes a pontos fixos durante 50 segundos, e alta correlação nas medidas quando comparado ao Optotrak. No segundo estudo avaliamos o Kinect para aquisição de dados dinâmicos, comparandoo novamente com o Optotrak, em cinco diferentes movimentos articulares, e em três diferentes velocidades de execução. Os resultados indicam que a diferença entre as medidas obtidas...
Keywords: Motor ability; Capacidade motora; Capacidade motora - Testes; Video games; Xbox video games